Obstacles to Regional Government in Distributing Superior Oil Palm Seedlings in Bungo Regency (International Journal of Economics and Management Research, 2026)
The oil palm plantation sector is one of the most significant agribusiness contributors to Indonesia's national economy, including in Bungo Regency, Jambi Province. Despite its strong potential, the income of oil palm farmers in this region remains suboptimal. Several challenges hinder productivity, such as the use of low-quality seedlings, inadequate cultivation practices, and land conversion from previous crops such as rubber or secondary forest (tanah sesap). This study aims to explore an effective model for improving the use of superior oil palm seeds and supporting local government programs to enhance farmers' income levels. The research utilizes primary data, secondary data, and other relevant information collected during the 2019–2024 period. The data were analyzed using descriptive analysis and a qualitative approach to gain a comprehensive understanding of field conditions, cultivation systems, and key issues faced by farmers. The findings indicate that the adoption of superior seedlings, supported by structured cultivation planning, technical training, and local government interventions, has strong potential to significantly improve productivity and increase farmers' income. This study is expected to serve as a reference for developing sustainable oil palm plantation programs in Bungo Regency.